Relationship of research attitude and knowledge with academic achievement of prospective teachers in Pakistan - Rafiq, Noreen; Ahmad, Shakil; Iqbal, Abid; Ashiq, Murtaza (Frontiers in Education, 2025)
BackgroundIn a data-driven society, educators are expected to excel in the field of research so that they may examine problems that they are facing and find their solutions. The current study aims to examine the relationship of prospective teachers’ research attitude and knowledge with their academic achievement in research courses. This quantitative exploration is based on a self-report survey for which a correlational research design was used.MethodMulti-stage sampling technique was employed to select a sample of 540 prospective teachers from two public and two private universities of Lahore district. Two instruments (Attitude toward Research and Research Knowledge Scale) were used to measure their level of research attitude and knowledge. The academic achievement was measured through the Grade Point Average (GPA) of prospective teachers in the research course.ResultsThe findings revealed that prospective teachers had a positive attitude toward research and a high level of research knowledge. Prospective teachers’ research attitude and knowledge had a significant positive relationship with their academic achievement in the research course. There was no significant difference between the attitude of public and private universities’ prospective teachers. However, their levels of research knowledge were significantly different.ConclusionProspective teachers with positive attitude toward research and good research knowledge were high achievers in the research course. It is suggested that educational institutes should organize research conferences, seminars, workshops and other research forums to enhance the prospective teachers’ knowledge, practical applications of research methodologies and understanding of research to promote a positive attitude toward research.